The Role of Community Service in Promoting Access to Justice: A Case Study of Free Legal Services in Region E - Flora, Henny Saida; Aiman, Muhammad; Lubis, Arief Fahmi; Puwa, Suryani Intan Pratiwi; Dewi, Putri Maha (PT Inovasi Pratama Internasional, 2025)
This qualitative study explores the role of community service in enhancing access to justice through free legal aid programs in Region E, an area marked by socioeconomic disparities and limited legal resources. Using semi-structured interviews with 15 legal practitioners and 20 beneficiaries, along with documentary analysis of program reports from 2020 to 2025, the research investigates how these initiatives empower marginalized populations and address systemic barriers. The findings reveal three key themes: (1) empowerment through increased legal literacy, enabling beneficiaries to better understand and assert their rights; (2) building trust between communities and formal legal institutions by providing accessible, culturally sensitive services; and (3) persistent challenges including funding shortages, staffing limitations, and infrastructural constraints such as poor internet connectivity. The study highlights that free legal services not only resolve individual legal issues but also contribute to broader social awareness and collective empowerment. However, the sustainability and scalability of these programs depend on stronger institutional support and innovative approaches, such as digital outreach and partnerships with local authorities. This research contributes to the discourse on grassroots legal empowerment by providing empirical insights from a rural context often underrepresented in justice studies. The findings offer practical recommendations for policymakers, NGOs, and legal professionals aiming to improve justice accessibility through community-driven efforts. Ultimately, the study underscores the critical importance of community service initiatives in bridging justice gaps and fostering inclusive legal systems.